Deep incorporation of corn straw benefits soil organic carbon and microbial community composition in a black soil of Northeast China. (26th February 2022) - Zhu, Fangni; Lin, Xinxin; Guan, Song; Dou, Sen
Abstract: 'Deep incorporation of corn straw' (CSDI) is to concentrate the burial of corn straw into the subsurface soil layer (20–40 cm) and to break the plough pan, thereby creating a loosened plough layer (0–20 cm) and a fertile subsurface soil layer. However, its impacts on soil organic carbon (SOC) and the microbial community remain poorly understood. A field experiment was conducted to investigate the effects of 1‐year CSDI (CD1), 3‐year CSDI (CD3) and 5‐year CSDI (CD5) on soil aggregates and aggregate‐associated SOC, as well as bacterial and fungal community characteristics (examined by the high‐throughput gene sequencing method). The results demonstrated that SOC and soil fungal diversity were decreased by CD1, but increased by CD3 and CD5. Compared with the control, CD5 promoted 2–0.25 mm soil macroaggregation, significantly increased SOC by 8.94% and aggregate‐associated SOC by 5.96%–8.84%, consequently improving the physical protection of SOC by soil aggregates. CD3 and CD5 enhanced the richness and diversity of soil bacteria and fungi, and altered community composition. For soil bacteria, the relative abundance of Acidobacteria and Chloroflexi was increased, while that of Firmicutes, Gemmatimonadetes, Sphingomonas and Bacillus was decreased. For soil fungi, the relative abundance of Ascomycota, Zygomycota, Mortierella and Fusarium was greatly improved, but that of Basidiomycota was reduced. These obvious variations in microbial community structure were beneficial to straw degradation and SOC accumulation. Overall, the optimization of microbial community with CSDI plays a positive role in promoting soil organic matter, nutrient cycling and carbon sequestration, and thus improving soil fertility.